Understanding Parents’ Knowledge Towards Childhood Immunisation: A Pilot Study - Nurul Azmawati Mohamed @ Abd Aziz; Zarini Ismail; Ramli, Shalinawati (Universiti Sains Islam Malaysia, 2024)
Immunisation programmein Malaysia started in the 1960s.To date,there are seven types of vaccines provided freely by the Ministry of Health for children from birth until age of 7years. After the introduction of the programme,dramatic reduction in mortality and morbidity related to infectious diseases have been observed.Of concern,there has been increasing number of parents recently who are against childhood vaccination.The impact of the decision is massive,not only to their own children,but also to the other children.Parents’ knowledge is the major factor that contribute to their decision for immunisation. Therefore,parents should be well-informed on the purpose of immunisation,so that they would not easily be deceived by anti-vacciners propaganda,particularly in the social media.